The Treatment of Water Using Activated Carbon Adsorption and Sand Filtration: Physical Characteristics Analysis for Clean Water Production - Imaniah Sriwijayasih; Anda Iviana Juniani; Dika Rahayu widiana; Fitroh Resmi; Septaviola Dini Utami; Eky Novianarenti; Anisa Ayuk Lestari; Raisha Risandra Rabbani (Poltanesa, 2026)
The Kalibaru River in Indonesia faces significant pollution challenges due to industrial and human activities, threatening ecosystem balance and water quality. To address this, a sand and carbon filter-based water filtration system is employed to improve water quality to grade 2 clean water standards.The method involves filtration using sand filters, carbon filters. Results show improved water quality with parametersThe decrease in turbidity from 6 NTU (March) to 5 NTU (June) indicates the filtration system's ability to remove suspended particles. Additionally, the decrease in electrical conductivity from 179.83 umhos (March) to 173.41 umhos (June) and TDS from 95.9 mg/L (March) to 92.7 mg/L (June) shows the system's ability to reduce dissolved ion concentrations.The stability of pH between March (7.58) and June (7.38) indicates that the filtration system does not affect the water's pH balance, remaining within the class 2 water quality standard (6-9). The relatively stable water temperature between March (27.5°C) and June (27°C) also shows that the filtration system does not significantly affect the water temperature  with Indonesian Government Regulation No. 82 of 2001.The system effectively removes contaminants, reduces turbidity, and kills pathogenic bacteria, making the water suitable for recreation, freshwater aquaculture, livestock, agriculture, and other uses. Regular monitoring and maintenance are necessary to sustain water quality.Indonesia's river water quality has been declining due to industrial pollution, pesticide and fertilizer use, and plastic waste. To combat this, efforts are being made to improve wastewater management, promote sustainable agriculture practices, and enhance public awareness.